If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + 6 + 9 = 13 + 5f Reorder the terms: 6 + 9 + 3f = 13 + 5f Combine like terms: 6 + 9 = 15 15 + 3f = 13 + 5f Solving 15 + 3f = 13 + 5f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-5f' to each side of the equation. 15 + 3f + -5f = 13 + 5f + -5f Combine like terms: 3f + -5f = -2f 15 + -2f = 13 + 5f + -5f Combine like terms: 5f + -5f = 0 15 + -2f = 13 + 0 15 + -2f = 13 Add '-15' to each side of the equation. 15 + -15 + -2f = 13 + -15 Combine like terms: 15 + -15 = 0 0 + -2f = 13 + -15 -2f = 13 + -15 Combine like terms: 13 + -15 = -2 -2f = -2 Divide each side by '-2'. f = 1 Simplifying f = 1
| 15x^2-180x+480=0 | | 8x=7x-1 | | a^6+7a^3+6=2 | | 6g+21=39 | | -2(2x-10)+29=3x | | a^2+10a=-21 | | -2(6-10n)=10(n-6) | | 8y=27 | | 5x-9=45 | | C(m)=0.4m+35 | | 17+t=43 | | 25-p=75 | | 7.8(x-4)=-0.2x+8.8 | | 12(x+3)-3=117 | | 16-p=2 | | 4x+19+111+6x-8=90 | | 25p=75 | | 4x+19+111+6x-8=180 | | 4(2*4+3)-3x=47-3(x+1) | | 18=6-3x | | 11d+10=6a | | 12-3x=2x | | 6x-8+111=4x+19 | | 3p=81 | | 4x+19+111=6x-8 | | 2v^2+11v+5= | | 3+p=81 | | (2x+4)x+19=0 | | 5u+25.00=40.00 | | 3c-17ifc=20 | | 40.00+5u=25.00 | | (5x^2+6x)(12x^2-5x-2)=0 |